Designs of Maggot Rotary Dryer to Support Alternative Feed Production - Kamaludin, Muhamad; Agus Haris Abadi; Masri Bin Ardin; Rian Dwi Aji Saputro; Nurizzi Rifqi Ferdian; Dadang Hafid; Asep S. Setyadin (Politeknik Piksi Ganesha Indonesia, 2025)
The growth of maggot cultivation as an alternative feed source is increasing in response to the demand for sustainable organic waste management solutions. However, the drying process remains a major challenge, especially for small and medium-scale operations. This study aims to design and develop a 20-kg capacity rotary maggot dryer that is efficient, energy-saving, and suitable for community-scale production. The design method includes user needs analysis, material selection, CAD-based design simulation, and testing tool performance. The results indicated that the dryer can reduce maggot moisture content within an average drying time of 3 hours at 60–70°C with relatively low energy consumption. This innovation is expected to improve maggot production efficiency and promote appropriate technology for sustainable alternative feed development at the community level.